REDUCTION EYE RED DIGITAL IMAGE EFFECT WITH ALGORITHM INTENSITY COLOR CHECKING - Amran Sitohang (Sean Institute, 2018)
The results of a photo either with a normal camera or a digital camera when taken from with high exposure to people, often produce red spots on the pupils of the term with the red-eye effect on digital photos. This of course causes the photos to be not good. With a particular software that functions as an image processor it can easily remove the red-eye just by using a tool called the red-eye effect that is reduced. So with this program the results of photos with a digital camera can be edited to eliminate the red-eye effect before printing. The red-eye effect is reduced using the intensity color checking algorithm in the process of replacing the red pixel images and then replacing them with grayish-black according to the resulting intensity process. Program that can reduce the red-eye effect with the intensity color checking algorithm by processing certain selected regions. The image results can then be printed or saved again in JPG format.